Human metabolite-derived alkylsuccinate/dilinoleate copolymers: from synthesis to application - Jäger, Alessandro; Donato, Ricardo K; Perchacz, Magdalena; Donato, Katarzyna Z; Starý, Zdeněk; Konefał, Rafał; Serkis-Rodzeń, Magdalena; Raucci, Maria G; Fuentefria, Alexandre M; Jäger, Eliézer (Journal of materials chemistry. B, 2020)
The advances in polymer chemistry have allowed the preparation of biomedical polymers using human metabolites as monomers that can hold unique properties beyond the required biodegradability and biocompatibility. Herein, we demonstrate the use of endogenous human metabolites (succinic and dilinoleic acids) as monomeric building blocks to develop a new series of renewable resource-based biodegradable and biocompatible copolyesters. The novel copolyesters were characterized in detail employing several standard techniques, namely 1H NMR, 13C NMR, and FTIR spectroscopy and SEC, followed by an in-depth thermomechanical and surface characterization of their resulting thin films (DSC, TGA, DMTA, tensile tests, AFM, and contact angle measurements). Also, their anti-fungal biofilm properties were assessed via an anti-fungal biofilm assay and the biological properties were evaluated in vitro using relevant human-derived cells (human mesenchymal stem cells and normal human dermal fibroblasts). These novel highly biocompatible polymers are simple and cheap to prepare, and their synthesis can be easily scaled-up. They presented good mechanical, thermal and anti-fungal biofilm properties while also promoting cell attachment and proliferation, outperforming well-known polymers used for biomedical applications (e.g. PVC, PLGA, and PCL). Moreover, they induced morphological changes in the cells, which were dependent on the structural characteristics of the polymers. In addition, the obtained physicochemical and biological properties can be design-tuned by the synthesis of homo- and -copolymers through the selection of the diol moiety (ES, PS, or BS) and by the addition of a co-monomer, DLA. Consequently, the copolyesters presented herein have high application potential as renewable and cost-effective biopolymers for various biomedical applications.
Keywords: kyselina jantarová; Humans; Polyesters; antifungální látky; Succinic Acid; alkylace; Alkylation; Linoleic Acid; Cell Adhesion; lidé; proliferace buněk; kyselina linolová; buněčné linie; Biocompatible Materials; polyestery; Cell Line; Antifungal Agents; Cell Proliferation; biokompatibilní materiály; buněčná adheze